2019
DOI: 10.3389/fphys.2019.00422
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of an Organized Cementum-Periodontal Ligament-Like Complex Using Scaffold-Free Tissue Engineering

Abstract: A major challenge in regenerating periodontal tissues is emulating its complex structure containing both mineralized and soft tissues. In this study, scaffold-free tissue constructs engineered using periodontal ligament cells (PDLCs), which contain a population of adult stem/progenitor cells, self-assembled into an organized multi-tissue structure comprising a mineralized cementum-like core enclosed within a periodontal ligament (PDL)-like tissue. Scaffold-free engineered constructs were formed by culturing hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…The cell‐sheets can completely maintain the ECM protein between cells and form a three‐dimensional structure without any scaffold material, thereby increasing post‐implantation survival 17,18 . Tsumanuma et al observed the newly formed cementum and well‐aligned fibrous structure after implanting PDL cell (PDLC) sheets and β‐tricalcium phosphate complex into the canine wall defect for 8 weeks, 19 and Basu et al demonstrated that implantation of PDLC sheets into immunocompromised mice can form a cementum‐periodontium‐like composite structure 20 . These findings indicate that the PDLC sheets have great potential for the application of periodontal tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…The cell‐sheets can completely maintain the ECM protein between cells and form a three‐dimensional structure without any scaffold material, thereby increasing post‐implantation survival 17,18 . Tsumanuma et al observed the newly formed cementum and well‐aligned fibrous structure after implanting PDL cell (PDLC) sheets and β‐tricalcium phosphate complex into the canine wall defect for 8 weeks, 19 and Basu et al demonstrated that implantation of PDLC sheets into immunocompromised mice can form a cementum‐periodontium‐like composite structure 20 . These findings indicate that the PDLC sheets have great potential for the application of periodontal tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…[103] In fact, this scaffold-free tissue engineering method favors PDLderived cells self-assembling in a structure that mirrors the complexity of periodontium. [104] More importantly, organized cell structures are maintained in vivo where they express key molecules required for PDL remodeling. These structures are also suitable for a co-culture of additional cell types.…”
Section: Scaffold-free Engineering Approaches To Study Local Tissue Cmentioning
confidence: 99%
“…A myriad of techniques are available to fabricate scaffolds including solvent casting 5 , freeze casting 6 , freeze drying 7 , electrospinning 8 , gas foaming 9 , particulate-leaching 10 , melt molding 11 , phase separation 12 , and self-assembly 13 and sol–gel methods 14 . However, most techniques are limited by their poor control over scaffold design, architecture, pore network and pore size.…”
Section: Introductionmentioning
confidence: 99%